POTENSI DAERAH DAN DAYA SAING DAERAH BERDASARKAN ANALISIS TIPOLOGI KLASSEN - Andi Hendrawan (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2020)
Regional economic competitiveness intends to obtain sustainable economic growth, namely developing superior sectors based on the potential and needs of the region whose aim is to improve people's welfare. The purpose of this study is to determine the leading sector based on GRDP in Cilacap Regency. The research method is exploratory research in the activity of compiling regional competitiveness. This is to explore the development of regional sectors by identifying and analyzing regional potentials that can be developed to improve regional competitiveness. Klassen's Typological Analysis is useful for identifying maps of macroeconomic potential. Through the Klassen Typology Analysis, regional sectoral potential based on GRDP data can be mapped. Klassen's Typological Analysis classifies a growth based on (g) and the contribution of a particular sector to the total regional GRDP. Based on Klassen's typology analysis, the main sector of Cilacap Regency is the construction sector and the Large and Retail trade sector, Car and Motorcycle Repair, this is very possible because Cilacap Regency is an industrial city so that construction activities are one of Cilacap's mainstayst.